Endoscopic mucosa-sparing lateral dissection for treatment of gastric submucosal tumors: a prospective cohort study - Li, Yue; Zhang, Qiang; Zhu, Chaojun; Luo, Yuchen; Han, Zelong; Qing, Haitao; Cai, Jianqun; Li, Ling; Huang, Ying; Liu, Side (Endoscopy, 2018)
Background In our previous work, we developed a modified method for the removal of gastric submucosal tumors (SMTs), called endoscopic mucosa-sparing lateral dissection (EMSLD). This prospective study aimed to evaluate the efficacy and postoperative outcomes of EMSLD.Methods We prospectively enrolled 25 consecutive patients with gastric SMTs, who received EMSLD treatment. Clinicopathological characteristics and operation-related outcomes were analyzed.Results The mean age of patients was 49.3 ± 9.7 years, and the mean tumor size was 14.6 ± 6.1 mm. En bloc resection was achieved in all cases. The mean procedure time was 47.3 ± 25.9 minutes, and the estimated blood loss was 4.8 ± 3.5 mL. Endoscopic full-thickness resection was performed in six patients (24 %) because the tumors originated from the deep muscularis propria layer. All perforations and resection defects were successfully closed by the retained mucosa and endoclips. No serious complications related to EMSLD were encountered during or after the procedure.Conclusions EMSLD was reliable and effective for the removal of gastric SMTs. However, large-scale randomized controlled trials are needed.